The character of Gareng’s Gecul movement in Sumar Bagyo version of dance - Wulandari, Dewi; Slamet, Slamet (Harmonia: Journal of Arts Research and Education, 2017)
The aim of this research is to describe and analyze the character of gerak gecul performed by Sumar Bagyo in expressing Gareng. This is considered unique since Sumar Bagyo developed his own version of the movement. Qualitative research by using ethnochoreology approach is used in this research. It is done by using some concepts and theories to support the research. Those theories included social changing theory by A. Boskoff, concept of solah ebrah by Slamet, that is combined with effort-shape by Ann Hutchinson, physiognomy concept by Prasetnyono, mimic and expressive gestures by Morris. Gecul movement which is performed, has its own characteristic that makes it different from other Gareng characters. Based on its wanda (Gareng in Purwa puppet), Sumar Bagyo belongs to wanda kancil since it has the characters of: praupan tengadah, medium face, round head, thin lips, wide forehead/ manyul (Javanese), ovoid nose, up lips, gondhok neck, flat stomach, small slouch body, ndetheng body. Gecul Gareng movement in Sumar Bagyo has the movement motives of gejig, mlaku ceko, sikil mingkup buka, seleh asta, nyorok, nikelwarti, besut alusan, besut gagahan, uncal sikil, geol, and srisig. Those movements always appear in the three types of Sumar Bagyo, either in puppet stage with Gareng identity, or outside of the puppet stage by taking off the Gareng identity.